A case report of pyomyoma: radiological diagnosis of a potentially fatal complication of uterine leiomyoma. - MY, Mubarak; MD, Noordini (IIUM Medical Journal Malaysia, 2008)
Pyomyoma (suppurative leiomyoma) is a rare complication of uterine leiomyoma. It results from infarction and infection of a leiomyoma. It may lead to diagnostic and therapeutic difficulties with potential complications such as bacteraemia, uterine rupture, compressive effect to adjacent structures and even death. We report a case of pyomyoma based on the Ultrasound (US) and Computed Tomography (CT) findings and literature review on the subject.